ARTIFICAL REPRODUCTION TECHNOLOGY IN THE VIEW OF CONTEMPORARY SUNNY AND SHIA JURIST - Fahmi Hasan Nugroho (Jurnal Ilmiah Pesantren, 2017)
Artificial Reproduction Technology (ART) get mixed response from contemporary Sunni and Shia jurist. The majority of Sunni scholars claimed the permissibility of it with several requirements that must be fulfilled, and some other Sunni scholars claimed makru>hand even prohibit it. On the other hand, the Shia scholars claimed the permissibility of ART but they differ in terms of the involvement of third parties in terms of donor sperm, donor egg and surrogacy. This article shows the view of Sunni and Shia to ART as well as various issues related thereto. This article also proves that the use of reasonable argument is more dominant in the Shia scholars than Sunni scholars whom more bound to the revelation texts and the jurisprudential legal maxim. This study uses Islamic legal theory approach with a focus on the fatwas and opinions of the scholars of Sunni and Shia in this field.